EVALUATING THE PROFESSIONAL ADAPTATION AND PRACTICAL PERFORMANCE OF PRESCHOOL EDUCATORS TRAINED IN A DUAL EDUCATION SYSTEM - Rakhimova Farogathon Ikromovna (Web of Journals Publishing, 2025)
This article provides an in-depth theoretical assessment of the effectiveness of the dual education model in preparing preschool educators (specialty 40110104). Focusing on two critical, interdependent outcomes—professional adaptation and practical performance—the study analyzes how this model addresses the persistent theory-practice gap. It theoretically contrasts the developmental trajectory of dual education trainees with their traditionally-trained counterparts, examining the mechanisms by which “situated learning” and continuous workplace immersion mitigate professional “reality shock”. The article highlights the pivotal role of the in-company mentor ('ustoz-tarbiyachi') in facilitating socio-professional integration and accelerating the development of adaptive expertise. Finally, the study concludes that the dual education system offers a superior pedagogical framework for developing competent, resilient, and “work-ready” educators, providing clear recommendations for curriculum reform in Uzbekistan's vocational education sector.
Keywords: Dual education, preschool educators, professional adaptation, practical performance, work-integrated learning, situated learning, theory-practice gap, vocational education.